Boosted kernel search: Framework, analysis and case studies on the economic emission dispatch problem - Dong, Ruyi; Chen, Huiling; Heidari, Ali Asghar; Turabieh, Hamza; Mafarja, Majdi; Wang, Shengsheng (Knowledge-based systems, 2021)
In recent years, a variety of meta-heuristic nature-inspired algorithms have been proposed to solve complex optimization problems. However, these algorithms suffer from the shortcoming that multiple hyperparameters need to be set carefully. Therefore, to solve the problem, the kernel search optimization (KSO) algorithm inspired by the kernel method has been proposed. KSO can simplify the optimization process by transforming the optimization process of nonlinear function into the linear optimization process. Despite its advantage, the original KSO requires a large amount of computation, and has no powerful exploitation search, resulting in its inability to obtain more accurate results. In the present study, a local search of the hill-climbing algorithm is adopted, and the calculation of the kernel parameter is simplified to improve the original KSO. In an experiment using 50 benchmark functions, the new algorithm outperformed KSO and some well-known algorithms in accuracy and running time. Moreover, when applied in the real-world economic emission dispatch problem, the improved algorithm achieved a better performance than other algorithms compared. An online repository will support this research at https://aliasgharheidari.com. •The kernel parameter’s calculation is simplified to improve KSO algorithm.•A local search of the hill-climbing algorithm is utilized for KSO’s exploitation.•IKSO is compared with some classic and popular MAs on benchmark functions.•The performance of IKSO is evaluated in different dimensions and types.•IKSO has achieved a much better performance than other literature MAs in EED problem.